Gender construction and femininity negotiation among female Muay Thai and Mixed Martial Arts athletes - Ahmad Rithaudin; Heru Nugroho; Budiawan Budiawan (Universitas Sriwijaya, 2026)
Research Problems: Sports not only have a function to achieve ideal physical goals and victories, but also serve as a cultural arena that involves gender issues. However, research on gender and femininity in combat sports in Indonesia is still very limited. Research Objectives: This study aims to describe the construction of gender and the negotiation of femininity of female Muay Thai and Mixed Martial Arts combat athletes. Methods: The research method is qualitative with a phenomenological approach. Data were obtained from semi-structured interviews with four female combat athletes, consisting of two amateur athletes and two professional athletes. The data were analyzed based on the reference of Miles and Huberman, which includes data reduction, presentation, and drawing conclusions. Results: The results obtained from this study are the description of forms of negotiation by female athletes based on four themes that define the study's scope. Conclusion: The conclusion of this paper is that female combat athletes negotiate the femininity and masculinity inherent in themselves. Female fighters do not completely reject feminine norms, but negotiate them through the integration of religiosity, morality, and professionalism. The bodies of female fighters become spaces where physical masculinity and cultural femininity do not negate each other, but coexist in a hybrid manner.